Configuration development and optimization of hydraulically interconnected suspension for handling and ride enhancement. (February 2022) - Damavandi, Arash Darvish; Masih-Tehrani, Masoud; Mashadi, Behrooz
In this study, among 180 possible hydraulically interconnected suspension configurations, non-symmetric cases were eliminated and 24 potential configurations were selected for further investigation. A 14-DOF vehicle model capable of generating handling and ride motions is developed. At different manoeuvres and road inputs, the handling and ride performances are investigated for 24 configurations. Six hydraulic parameters are then optimized by the application of genetic algorithm in order to improve the ride. The handling performance is also investigated and results have shown that only four configurations provide better ride and handling performances simultaneously. The bounce acceleration response is shown to be reduced up to 47% for the four selected configurations. The roll and pitch angle responses were also reduced around 3% and 18% respectively. Four optimized configurations were also investigated under two sever ride and handling manoeuvres. It is shown that, for the vehicle with the optimized interconnected hydraulic suspension, the bounce acceleration response for a random road test is reduced up to 27% and the roll angle is reduced up to 18% for a side wind test.